The Impact of Study Club on English Speaking Skills: Student Perceptions (Tamaddun, 2025)
This study investigates the impact of the English Study Club at Al-Qolam University on students’ speaking skills, addressing the problem of limited speaking proficiency due to lack of confidence, insufficient practice opportunities, and unsupportive environments. Employing a descriptive qualitative approach, data were collected through in-depth interviews with five informants, including one administrator and four members (senior and junior), to explore participation dynamics, motivations, challenges, and outcomes. Findings reveal that the Study Club significantly enhances speaking fluency and confidence by providing a safe, inclusive space for regular practice through diverse activities like debates, presentations, and speaking games, with notable improvements in communicative behavior, particularly among shy students. However, challenges such as inconsistent participation, fear of making mistakes, and technical limitations in vocabulary and grammar persist, necessitating targeted strategies to sustain engagement and address skill gaps. The study concludes that the English Study Club is an effective platform for improving speaking skills, but its success depends on fostering consistent participation, reducing psychological barriers, and incorporating structured technical support to maximize its impact on students’ language proficiency.